Practical PHP and MySQL Web Site databases : a simplified approach - West, Adrian W. (Apress Imprint: Apress, 2013)
Practical PHP and MySQL Website Databases is a project-oriented book that demystifies building interactive, database-driven websites. The focus is on getting you up and running as quickly as possible. In the first two chapters you will set up your development and testing environment, and then build your first PHP and MySQL database-driven website. You will then increase its sophistication, security, and functionality throughout the course of the book. The PHP required is taught in context within each project so you can quickly learn how PHP integrates with MySQL to create powerful database-driven websites. Each project is fully illustrated, so you will see clearly what you are building as you create your own database-driven website. You will build a form for registering users, and then build an interface so that an administrator can view and administer the user database. You will create a message board for users and a method for emailing them. You will also learn the best practices for ensuring that your website databases are secure. Later chapters describe how to create a blog, a product catalog, and a simple e-commerce site. You will also discover how to migrate a database to a remote host. Because you are building the interactive pages yourself, you will know exactly how the MySQL and PHP work, and you will be able to add database interactivity to your own websites with ease.